A Comment on Bai, Jia &, Yang (2023) Web of Power: How Elite Networks Shaped War and Politics in China - Tom Buchot; Mathieu Couttenier; Lucile Laugerette; Elisa Mougin; Alexandre Verlet (Institute for Replication (I4R), 2024)
Bai et al. (2023) examine the impact of individual networks on state building, focusing on the role of the leader Zeng Guofan during the Taiping Revolution in China between 1850 and 1864. In their main results, the authors demonstrate that being connected to Zeng increases the number of fatalities during the war after his assumption of power, with point estimates being significant at the 1% or 5% level. They also find a positive and significant effect of connections to Zeng among Hunan people on the number of national-level office positions, with point estimates significant at the 1% level. First, we reproduce the paper's main findings and identify minor inaccuracies in the codes that need fixing for the proper reproduction of some tables. However, these issues do not significantly impact the overall results. Second, we conduct additional checks and argue that the results are robust to variations in the number of fixed effects but highly dependent on the choice of econometric specification. We employ alternative models more suitable for data with a substantial number of zeros, revealing a decrease in the magnitude and significance of the estimates. Last, we perform spatial robustness checks, confirming the absence of spatial correlation between Hunan county and its neighboring regions, as suggested by the authors.
Keywords: 330